The Policy of The Regional Supervisory Board in Overcoming Business Competition Problems in The Determination of Honorarium By Notaries in The Kuningan District - Mochamad Sesar Dwisepta; Kadar Pamuji; Kartono Kartono (Authentica, 2021)
The role of the Regional Supervisory Board (hereinafter referred to as Supervisory) in supervising Notary is very important, the goal is that Notary in carrying out their duties in their positions remain within the corridors of statutory regulations and the code of ethics. This study aims to determine the extent of the role of the Supervisory in supervising Notary in determining Honorarium outside the Rules of Notary Profession and under association provisions. This type of research is normative juridical. The method used in this research is literature study and interviews by interviewing several Notary and the chairman of the Regional Supervisory Board as respondents. The data obtained were analyzed using qualitative analysis techniques and then described. The results of the study show that the Regional Supervisory Board regarding its role in supervising Notary who determine the honorarium under the stipulations of the association and the Law on Notary Position can be summoned if there is a prior report from the public, however, the Supervisory should work and be active in terms of supervising Notary, because the Supervisory according to article 1 number 6 of the Rules of Notary Profession has given the authority to guide Notary.Keywords: Regional Supervisory Board; Notary; Role; Honorarium